Diethyl 2,6-dimethyl-4-phenyl-1,4-dihydropyridine-3,5-dicarboxylate - Bai, Ming-Sheng (International Union of Crystallography, 2009)
The title molecule, C(19)H(23)NO(4), was synthesized by the reaction of benzaldehyde, ethyl acetoacetate and NH(4)HCO(3). The dihydropyridine ring adopts a flattened boat conformation and the plane of the base of the boat forms a dihedral angle of 88.78 (9)° with the phenyl ring. The packing is stabilized by strong intermolecular N—H⋯O and weak intermolecular C—H⋯O hydrogen bonds.